2019
DOI: 10.1103/physrevd.99.124048
|View full text |Cite
|
Sign up to set email alerts
|

pp -waves as exact solutions to ghost-free infinite derivative gravity

Abstract: We construct exact pp-wave solutions of ghost-free infinite derivative gravity. These waves described in the Kerr-Schild form also solve the linearized field equations of the theory. We also find an exact gravitational shock wave with non-singular curvature invariants and with a finite limit in the ultraviolet regime of non-locality which is in contrast to the divergent limit in Einstein's theory. I. INTRODUCTIONAmong the small scale modifications of Einstein's theory of General Relativity (GR), infinite deriv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 65 publications
2
35
0
Order By: Relevance
“…It was shown that IDG may avoid not only black-hole type singularities [26][27][28][29][30][31][32][33], but also topological defects such as p branes [34], cosmic strings [35], and NUT-like singularities [36]. The exact pp-wave solutions have been studied in [37].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that IDG may avoid not only black-hole type singularities [26][27][28][29][30][31][32][33], but also topological defects such as p branes [34], cosmic strings [35], and NUT-like singularities [36]. The exact pp-wave solutions have been studied in [37].…”
Section: Introductionmentioning
confidence: 99%
“…( 8), to put the metric (7) in the Kerr-Schild form ds 2 = d X 2 + dY 2 − du dV + du 2 (X 2 − Y 2 )d 2 u L/L. For these classes of metrics linear and non-linear theories coincide under certain conditions [48].…”
Section: Exact Nondiffracting Gravitational Wavesmentioning
confidence: 99%
“…[20] for a more general treatment including some non-maximally symmetric spacetime. It was also noticed that the presence of nonlocality can regularize infinities and many efforts have been made towards the resolution of black hole [17,18,[21][22][23][24][25][26][27][28][29][30][31][32][33] and cosmological [16,[34][35][36][37] singularities. At the quantum level, the high energy behavior of loop integrals has been investigated in [38][39][40][41] and properties of causality and unitarity in [42,43] and [44][45][46][47], respectively.…”
Section: Introductionmentioning
confidence: 99%